Silicon via nutrient solution modulates deficient and sufficient manganese sugar and energy cane antioxidant systems - Oliveira, Kamilla Silva [UNESP]; de Mello Prado, Renato [UNESP]; Checchio, Mirela Vantini [UNESP]; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2021)
Manganese (Mn) is highly demanded by Poaceae, and its deficiency induces physiological and biochemical responses in plants. Silicon (Si), which is beneficial to plants under various stress conditions, may also play an important role in plants without stress. However, the physiological and nutritional mechanisms of Si to improve Mn nutrition in sugarcane and energy cane, in addition to mitigating deficiency stress, are still unclear. The objective of this study is to evaluate whether the mechanisms of action of Si are related to the nutrition of Mn by modulating the antioxidant defense system of sugarcane plants and energy cane plants cultivated in nutrient solution, favoring the physiological and growth factors of plants cultivated under Mn deficiency or sufficiency. Two experiments were carried out with pre-sprouted seedlings of Saccharum officinarum L. and Saccharum spontaneum L. grown in the nutrient solution. Treatments were arranged in a 2 × 2 factorial design. Plants were grown under Mn sufficiency (20.5 µmol L−1) and the deficiency (0.1 µmol L−1) associated with the absence and presence of Si (2.0 mmol L−1). Mn deficiency caused oxidative stress by increasing lipid peroxidation and decreasing GPOX activity, contents of phenols, pigments, and photosynthetic efficiency, and led to the growth of both studied species. Si improved the response of both species to Mn supply. The attenuation of the effects of Mn deficiency by Si depends on species, with a higher benefit for Saccharum spontaneum. Its performance is involved in reducing the degradation of cells by reactive oxygen species (21%), increasing the contents of phenols (18%), carotenoids (64%), proteins, modulating SOD activity, and improving photosynthetic and growth responses.